The AMAR mechanism: nominal expressions in the Bantu languages are shaped by apposition and reintegration - Van de Velde Mark (Linguistics, 2022)
Nominal expressions in the Bantu languages have extraordinary typological characteristics. Their word order patterns are extremely diverse and some of the attested patterns are crosslinguistically very rare, or even unique. The same diversity can be found in the number of agreement marker paradigms. Equally remarkable are the prosodic idiosyncrasies found at the level of nominal expressions, especially the existence of prosodic boundaries associated with certain types of adnominal modifiers. Although logically unrelated, I argue that these typological characteristics can be accounted for by a single diachronic scenario here called the AMAR mechanism: a double tendency in the Bantu languages for the emergence of construals in which a nominalized modifier is in apposition to the phrase that contains its semantic head and for such appositional construals to be gradually reintegrated into a single nominal constituent. This paper aims to summarize some of the more remarkable typological characteristics of nominal expressions in the Bantu languages and to lay out the AMAR mechanism as a hypothetical diachronic explanation for many of them.